ANALISIS DETERMINAN PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Mutia Azizah Putri (2022)
The purpose of this study is to determine the effect of capital, liquidity, and credit risk on the profitability of banking companies listed on the Indonesia Stock Exchange between 2017 and 2020. This study uses a population of commercial banks listed on the Indonesia Stock Exchange (IDX) between 2017 and 2020. 2020. The saturated sample method was used to select the sample used in this study, which was 38 companies. The analytical technique used to conduct testing in this research is descriptive analysis and panel data regression analysis with the help of the Eviews version 10 program and a significance level of 5%. The results showed that capital and credit risk affected profitability, while liquidity did not affected profitability.